Asymmetry effects of government expenditure on education and impacts on economic growth - David Krizek; Kamila Vesela; Lucie Severova; Roman Svoboda (The European Journal of Comparative Economics (EJCE), 2022)
The aim of this contribution is to evaluate the efficiency of the Czech educational system. If we take into account the fact that investments are made in consideration of future returns, then it holds true that investments in the form of public finances invested in the education system are implemented with an eye to future returns, in particular in terms of future growth in economic performance. Based on the time series of the development of government expenditure on education, and with regard to the differentiation of this sector into primary, secondary, and tertiary education, this article evaluates the relationship of the government expenditures to the development of the gross domestic product for the Czech Republic in the period 1992-2015. A regression analysis method is used, modified by the ARIMA model and the time lags assumed for the relationship of these two variables. A relationship between growth in government expenditure on secondary education and subsequent growth in GDP has been demonstrated. According to the results, a time lag of 6 years can be expected between these occurrences.
Keywords: C12; D61; E62; H41; H52; 330; Czech Republic; Economic growth; Education; Government expenditures; Human capital